Product innovation strategies that support an organisation’s reset business strategy - Maithufi, Marang Norah (University of the Witwatersrand, Johannesburg, 2021)
Literature reveals that many organisations do not have well-communicated innovation strategies, or rarely articulate their innovation efforts to align with business strategies. In addition, research further emphasises that without innovation strategies, different parts of an organisation can find themselves pursuing conflicting priorities even in the existence of a clear business strategy. Organisation A, the case under study, has recently accounced its new refresh business strategy; in order to align itself with the changing business and consumer landscapes. The new business strategy focusses on value delivery through customer-centricity and market-focused businesses. The aim of this study is to ascertain product innovation strategies that can support Organisation A’s new business ambitions. Organisation A produces and markets a wide range of products, including chemicals; both commodity as well specialty chemicals. The products identifed for the study are polymers products, selected due to the unique challenges the products currently face; which include being commodity products at the mature stage of their product lifecycle. Parallel to this, these products have recently endured substantial environmental scrutiny relating to the increasing (polymers) plastics waste footprint in the environment and other externalities, with consumers thus demanding more environmentally sustainable product solutions. For a richer discovery, as well as uncovering perceptions which may influence how innovation is conducted at Organisation A, a qualitative single case study research strategy was pursued, via semi-structured interview schedules with Organisation A’ employees involved in and associated with the development, production, marketing, sales and support of polymers products under study. The study revealed that although innovation is widely acknowledged as important, the perceptions held within the business were that polymers product innovation was not a forefront imperative. This, according to the study participants, manifested as an environment that was unsupportive of product innovation endevours, a business that was overly risk-averse, internally focussed, and considered other categories of innovation such as manufacturing process innovations as more value creating than polymers product innovation efforts. Consequently, only incremental and sustaining product innovation activities that were perceived to not disrupt the business were embraced. Three strategies or opportunity areas are proposed, that Organisation A can explore for its polymers product innovation efforts to support the new business strategy
A research report presented in partial fulfillment for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, Johannesburg 2021
Keywords: Well-communicated innovation strategie; Innovation; Organisation; Product innovation strategies; Business strategy; UCTD; SDG-9: Industry, innovation and infrastructure